2009
DOI: 10.1530/eje-08-0623
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the 206M polymorphic variant of the SLC26A6 gene encoding a Cl− oxalate transporter in patients with primary hyperparathyroidism

Abstract: Objective: Primary hyperparathyroidism (PHPT) is often complicated by kidney stones. Hypercalciuria and urine oxalate excretion are considered risk factors for urolithiasis in PHPT as well as in idiopathic stone-formers. Recently, the anion-exchanger SLC26A6 has been involved in the oxalate metabolism.Design and methods: We tested the hypothesis that the 206M polymorphic variant of SLC26A6 gene might contribute to the risk of kidney stones in PHPT. DNA samples from 145 PHPT patients and 129 age-and sex-matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…PHPT has been recognized as a risk factor for impaired renal function, though the specific relationship between PHPT and this condition is not completely understood. Recent studies demonstrated that prolonged activation of the intrarenal inflammosome is responsible for the loss of kidney function in oxalate crystal nephropathy (15), which frequently occurs in PHPT (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…PHPT has been recognized as a risk factor for impaired renal function, though the specific relationship between PHPT and this condition is not completely understood. Recent studies demonstrated that prolonged activation of the intrarenal inflammosome is responsible for the loss of kidney function in oxalate crystal nephropathy (15), which frequently occurs in PHPT (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…SLC26A6, the gene coding for a sulphate transporter, is expressed in the human distal segments of the proximal tubules where it mediates oxalatedependent NaCl absorption. The 206M polymorphic variant of the SLC26A6 gene, whose encoded protein exhibits reduced activity, is not associated with kidney stones in PHPT patients, though it has been shown to be associated with less severe hypercalciuria in PHPT patients with stone formation, suggesting a role of SCL26A6 as contributor in kidney stone development in PHPT patients (35).…”
Section: Scl26a6mentioning
confidence: 97%
“…Only one candidate gene is associated with hypertension in human populations. In a study of the 206 M polymorphic variant of the SLC26A6 gene encoding a Cl(-)-oxalate transporter in patients with primary hyperparathyroidism, Corbetta et al [65] found that the SLC26A6 206M alleles were significantly related to the presence of hypertension.…”
Section: Chromosomementioning
confidence: 99%